Pengaruh Penggunaan Media Animasi Terhadap Kemampuan Membaca Permulaan Siswa Selama Pandemi Covid-19 - Maria Helvina; Agnes Yosefina Noeng; Frederiksen Novenrius Sini Timba (Universitas Islam Nahdlatul Ulama Jepara, 2022)
Beginning reading ability is a person's basic ability to master various fields of knowledge so it is very important to master. The ability to read at the beginning of grade 1 SDI Patisomba is still very low because students do not know letters well. This study aims to determine the effect of using animated media on initial reading skills in grade 1, students at SDI Patisomba during the covid-19 pandemic. This study used quantitative research methods with data collection techniques including tests and observations, analyzed using the t-test. From the results of the t-test calculation, there is a t count of 2.410 and a t-table with dk = 15 and the significant level = 0.05 is 1.753. It can be concluded that t count > t table (2,410>1,753) so that Ho is rejected and Ha is accepted, that is, there is an effect of using animation media on early reading skills in grade 1 students of SDI Patisomba. Based on the test results and observation results and analyzed using the T-test, it can be concluded that the students' initial reading ability and the learning outcomes of class 1 students have changed for the better after using animation media in the experimental class.